T-Cell Responses Are Associated with Survival in Acute Melioidosis Patients. - Kemajittra Jenjaroen; Suchintana Chumseng; Manutsanun Sumonwiriya; Pitchayanant Ariyaprasert; Narisara Chantratita; Piyanate Sunyakumthorn; Maliwan Hongsuwan; Vanaporn Wuthiekanun; Helen A Fletcher; Prapit Teparrukkul; Direk Limmathurotsakul; Nicholas P J Day; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Melioidosis is an increasingly recognised cause of sepsis and death across South East Asia and Northern Australia, caused by the bacterium Burkholderia pseudomallei. Risk factors include diabetes, alcoholism and renal disease, and a vaccine targeting at-risk populations is urgently required. A better understanding of the protective immune response in naturally infected patients is essential for vaccine design. METHODS:We conducted a longitudinal clinical and immunological study of 200 patients with melioidosis on admission, 12 weeks (n = 113) and 52 weeks (n = 65) later. Responses to whole killed B. pseudomallei were measured in peripheral blood mononuclear cells (PBMC) by interferon-gamma (IFN-γ) ELIspot assay and flow cytometry and compared to those of control subjects in the region with diabetes (n = 45) and without diabetes (n = 43). RESULTS:We demonstrated strong CD4+ and CD8+ responses to B. pseudomallei during acute disease, 12 weeks and 52 weeks later. 28-day mortality was 26% for melioidosis patients, and B. pseudomallei-specific cellular responses in fatal cases (mean 98 IFN-γ cells per million PBMC) were significantly lower than those in the survivors (mean 142 IFN-γ cells per million PBMC) in a multivariable logistic regression model (P = 0.01). A J-shaped curve association between circulating neutrophil count and mortality was seen with an optimal count of 4000 to 8000 neutrophils/μl. Melioidosis patients with known diabetes had poor diabetic control (median glycated haemoglobin HbA1c 10.2%, interquartile range 9.2-13.1) and showed a stunted B. pseudomallei-specific cellular response during acute illness compared to those without diabetes. CONCLUSIONS:The results demonstrate the role of both CD4+ and CD8+ T-cells in protection against melioidosis, and an interaction between diabetes and cellular responses. This supports development of vaccine strategies that induce strong T-cell responses for the control of intracellular pathogens such as B. pseudomallei.